Religious Harmony of Tengger Ethnic Perspective: Humanity and Spirituality in Minority Area: Harmoni Beragama Perspektif Etnis Tengger: Kemanusiaan dan Spiritualitas di Wilayah Minoritas - Ahmad Ulil Amin; Ida Fitri Anggarini; Muhammad Nabil Fahmi; Fina Lailatul Masruroh; Hilmi Fauzi; Naila Shofia (RABBAYANI: Jurnal Pendidikan dan Peradaban Islami, 2022)
Nahdlatul Ulama is a huge Muslim community in Indonesia that follows four religious resources that are Al-Qur’an, al-Sunnah, Ijma’ and Qiyas. On Fiqh following four Madhab (school of thought) such Imam Hanafi, Maliki, Syafi’i and Hambali. This ideology was found in minority areas and research related to the topic was limited. This study aimed to illustrate how Nahdlatul Ulama’s Fiqh Ibadah civilization has grown in minority areas. This qualitative narrative research study used observation, in-depth interviews, and documentation to collect primary data from five villagers of Tengger ethnics. The result shows that Tengger’s Muslims is a first learner (awam), it’s easier to implement amaliyah nahdliyah (Fiqh Ibadah) in their daily life, have a good relation to other religions (Hindu and Budha), have a cultural understanding, and live in harmony as one ethnic. Kata Kunci: Religious Harmony, Humanity, Spirituality, Tengger.